2012
DOI: 10.1371/journal.pone.0033839
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adherence to Screening Guidelines and of Diabetes Clinics Referral on Morbidity and Mortality in Diabetes

Abstract: Despite the heightened awareness of diabetes as a major health problem, evidence on the impact of assistance and organizational factors, as well as of adherence to recommended care guidelines, on morbidity and mortality in diabetes is scanty. We identified diabetic residents in Torino, Italy, as of 1st January 2002, using multiple independent data sources. We collected data on several laboratory tests and specialist medical examinations to compare primary versus specialty care management of diabetes and the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 24 publications
1
36
2
Order By: Relevance
“…More specifically, patients receiving structured or specialized diabetes care were more frequently treated according to the guidelines for type 2 diabetes [14,28,29]. The lower costs associated with managed care compared to usual care is comparable with recent studies showing that an increasing level of structured care was associated with decreased costs [15,30]. In these studies, information on costs was obtained by claims paid for covered health care use.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, patients receiving structured or specialized diabetes care were more frequently treated according to the guidelines for type 2 diabetes [14,28,29]. The lower costs associated with managed care compared to usual care is comparable with recent studies showing that an increasing level of structured care was associated with decreased costs [15,30]. In these studies, information on costs was obtained by claims paid for covered health care use.…”
Section: Discussionmentioning
confidence: 99%
“…13,[35][36][37] Inertia has been mostly thought to depend on (i) low GP propensity to changes, (i) poor care management DCU organization and eventually (iii) temporary unavailability of a specific drug 38,39 but our study showed that something eventually prevented even diabetologists from following best practice recommendations since the first visit.…”
Section: 2835mentioning
confidence: 62%
“…11,13,14,23 This is easily explained by the fact that diabetologists may focus more closely upon diabetes-related issues and have direct access to patient education resources and other specialists to collaborate with. Moreover, as apart from their renowned skills, Italian diabetologists hold power, being the only allowed prescribing innovative diabetes-related drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these guidelines can decrease all-cause mortality and cardiovascular morbidity (1). France, like other countries, has sought to improve diabetes management, specifically by establishing diabetes care networks (DCNs) that coordinate care, provide continuing medical education for health care professionals, and educate network patients.…”
Section: Membership In a Diabetesmentioning
confidence: 99%